Conflicting messages concerning current strategies against research misconduct in Japan: a call for ethical spontaneity. Issue 8 (20th April 2016) - Asai, Atsushi; Okita, Taketoshi; Enzo, Aya
Abstract : The Japanese government has asserted that the purpose of scientific activities is to search for the truth about the world and contribute to public interest of the humanities and claimed that research misconduct should occur under no circumstances ever. The revealing of each new case of research misconduct leads to the establishment of investigation committees and research guidelines, as well as punishments for the transgressors. However, we wonder if Japanese researchers are receiving different messages that might undermine the purpose of the former messages. First, Japan's policies on science and technology have been created to comprise an integration of merit-based evaluations, principles of competition and a concentrated and unbalanced distribution of research funding, leading to decreases in ordinary research funding for the researchers and an increase in fierce research competition. Second, Japanese government and society as a whole continue to send the researchers messages such as 'Only results matter', 'Be No. 1 as a top priority' and 'All we need now is scientific progress'. Third, cultural peculiarities may explain some of the actions relevant to research misconducts currently noted in Japan. We argue that it is essential to re-examine and improve the governmental policies and evaluation methods for research achievements need to be more multifaceted. In order to have the researchers act according to ethics, it is essential for them to reaffirm their objectives for working in the fields of science and medicine and the importance of balancing their personal profit with the greater cause for entering into this field.